The Effect of Modified Bombik Play Activities on Children’s Creativity: A Pre-Experimental Approach in Early Childhood Education - Farida Mayar; Sandra Sonita; Novia Sri Wilanda; Resa Tifeni Az-zahra; Kaniska Kristianti; Safia Safitri (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2025)
This study investigates the impact of modified bombik play activities on the creativity of children aged 5–6 years at Sani Ashilla II Kindergarten in Padang, Indonesia. Initial classroom observations indicated low levels of creativity, marked by children’s dependency on teacher models and lack of initiative. Employing a quantitative approach with a pre-experimental One Group Pretest–Posttest Design, the study involved 12 purposively selected participants from a population of 82. Data were gathered using structured observation sheets based on early childhood creativity indicators and analyzed with normality, homogeneity, and paired-sample t-tests. Results revealed a statistically significant improvement in creativity scores (t = 32.601 > t-table = 2.131; p < 0.05), demonstrating the effectiveness of the modified bombik play intervention. The findings underscore the pedagogical value of culturally contextualized and developmentally appropriate play-based media in fostering children's imagination, initiative, and expressive abilities. This study contributes to early childhood education by offering empirical support for integrating creative media innovations, particularly those that are low-cost, tactile, and visually stimulating. However, the absence of a control group and the small sample size limit the generalizability of the results. Moreover, the short intervention duration may not capture long-term developmental impacts. Future research is recommended to involve larger and more diverse samples, utilize experimental or quasi-experimental designs with control groups, and explore longitudinal effects of creative play. These steps would strengthen the evidence base for incorporating play-based strategies into national early childhood curricula and policy frameworks.